1990
DOI: 10.1209/0295-5075/11/7/005
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino-Resonant Oscillations in the Earth, and the ν eμ Ratio in Upward-Going Atmospheric Neutrino Fluxes

Abstract: We evaluate the conversion probability for neutrinos by solving the evolution equations with a numerical method, taking into account a density distribution of the Earth, and calculate an upward-going neutrino flux ratio (νe +ν̄e)/(νμ +ν̄μ) by using the recent values of atmospheric neutrino fluxes, where the updated ratios νμ/ν̄μ and νe/ν̄e have been taken into account. It is found that the ratio, including the effect of neutrino-resonant oscillations, can well explain the Kamiokande data for ϕ = 0° and 30°, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…However, the vacuum approximation is not adequate for neutrinos which travel in the earth matter for a large fraction of their path length. For these neutrinos one expects substantial deviations from the vacuum oscillation probability [42][43][44][45][46]23] when…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…However, the vacuum approximation is not adequate for neutrinos which travel in the earth matter for a large fraction of their path length. For these neutrinos one expects substantial deviations from the vacuum oscillation probability [42][43][44][45][46]23] when…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Neutrino oscillations in the Earth have been extensively studied in general and it has been suggested that neutrino oscillations in matter can severely alter the energy spectrum of a neutrino beam through the Earth for long baselines [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. For quite realistic calculations of the transition probabilities the Preliminary Reference Earth Model (PREM) or similar matter density profiles have been used [31,32].…”
Section: Introductionmentioning
confidence: 99%